Performance of uncoated WC-Co in end milling of Aluminium Silicon Carbide (AlSiC) - M. K. , Nor Khairusshima; Amin, A. K. M. Nurul; Ismail, Ahmad Faris (IIUM Press, 2011)
Metal matrix composite (MMC) with silicon carbide (SiC) reinforcement in pure aluminum matrix have found wide application in the automotive industry, especially in fiber reinforced pistons and particle-strengthened brake discs. Silicon carbide (SiC) reinforcement provides improved mechanical properties, thermal stability, high temperature formability and workability. However, the presence of the SiC phase in the structure causes serious machinability problems, especially when uncoated and coated WC-Co tools are used for their machining. High intensity of wear is attributed to high abrasive wear caused by the hard silicon carbide particles. In the current work investigations have been conducted to compare the performance of Poly Crystalline Cubic Diamond (PCD) tools with the conventional uncoated tungsten carbide-cobalt tool in machining aluminum silicon carbide (AlSiC) in terms of the applicable cutting speed ranges; chip morphology, tool wear rates and tool wear morphology, volume of metal removal allowed per tool life and attainable surface roughness.Most of the attentions are on those based on aluminum alloys and reinforced with silicon carbide [1]. AlSiC is preferred over ceramics because of the useful combination of properties such as high strength, ductility and high temperature resistance, whereas ceramics though are stiff and strong but are brittle in nature [2]. Li et al [3] found that aluminum alloys reinforced with silicon carbide particles are as much as three times more efficient than the un-reinforced aluminum alloys in defeating tungsten projectiles at 1.2 km/sec. In automobile industry, AlSiC has been considered for use in automobile brake discs and various components in internal combustion engines. Aluminum silicon carbide (AlSiC) is being widely used not only in aerospace and automobile industries, but also in the electronic industry, because of its unique thermal properties that are ideally suited for all electronic packaging applications. Though the list of favorable attributes for this new engineering material is quite impressive, the machinability of AlSiC is very poor because of the high tool wear rates associated with abrasive wear, which make it a class of difficult-to-machine advanced materials [4]. The silicon carbide phase, which has hardness in the range of tungsten carbide (WC),is mainly responsible for the high abrasive wear of the tool. Consequently the cutting edge of the tool which in course due to abrasion wear results in the formation of poor surface finish during turning [5]. During to the cutting tool edge [6]. In this process more particles join in with those already adhering AlSiC machining, under high temperature and pressure the particles of AlSiC adhere to form the so-called built during turning [7].